Implementation Of Strategic Plan To Improve The Quality Of Education Of MTS Muhammadiyah Lubuk Jambi Kuantan Singingi District - Irawati Irawati; Mohd. Winario (At-Tarbiyat, 2021)
The purpose of this study was to determine the implementation of strategic plans in improving the quality of education at Madrasah Tsanawiyah Muhammadiyah Lubuk Jambi, Kuantan Singingi Regency, the method used by the author in this study was field research, collecting data by means of direct interviews, documentation and direct observation in place of research, data analysis by means of qualitative descriptive analysis method. The results of the study indicate that there are three stages in the preparation of a strategic plan, namely: formulation of the vision, mission and objectives, implementation and monitoring strategies and evaluation of the quality of education. The implementation of these three stages is maximized in accordance with the management functions of planning, organizing, actuating and controlling in order to get good results and improve the quality of education at Madrasah Tsanawiyah Muhammadiyah Lubuk Jambi.